PENGARUH AUDITOR SWITCHING DAN KEPEMILIKAN MANAJERIAL TERHADAP PRICE BOOK VALUE (PBV) - Suryani, Ni Putu Nathania; Ardiana, Putu Agus (E-Jurnal Akuntansi; Vol 17 No 2 (2016), 2016)
This study aims to determine the effect of switching auditors and managerial ownership on firm value proxied by the price book value (PBV). This study was performed on companies listed on the Stock Exchange 2011-2015 period. This study uses multiple regression analysis with a total sample of 210 in the period of observation for five years. The sampling method used is the method nonprobability sampling with purposive sampling technique. Data analysis techniques used to solve the problem is multiple linear regression analysis. Based on the analysis found that the auditor switching and managerial ownership positively affects PBV. Companies that make the turn auditor tends to increase the company's value (PBV). The regression results on managerial ownership variable indicates that a high managerial ownership positively affects the value of the company is reflected through the PBV.
Keywords: Auditor Switching, Managerial Ownership, Price Book Value